Analysis of the S1 ← S0 and D0 ← S1 spectra in m-bromofluorobenzene via resonance-enhanced multiphoton ionization and slow electron velocity-map imaging spectroscopy. (February 2019) - Qin, Zhengbo; Ma, Naiyu; Ren, Yangdi; Zheng, Xianfeng; Yao, Guanxin; Zhang, Xianyi; Cui, Zhifeng
Highlights: Adiabatic excitation energy, IP and vibrational frequencies of m-BrFPh in S1 and D0 states were accurately measured and assigned. Franck-Condon simulations are performed to aid us in confidently assigning major vibrational modes in S1 and D0 states. The mixing of vibrational modes both between S0 & S1 and between S1 & D0 has been discussed. Abstract: Vibrations of m-bromofluorobenzene (m-BrFPh) in the first excited state (S1 ) and the cationic ground state (D0 ) are investigated by resonance-enhanced multiphoton ionization (REMPI) spectroscopy and slow electron velocity-map imaging (SEVI) spectroscopy, respectively. Quantum chemical calculations have been adopted to assign the observed vibrational bands, as well. The band origin of the S1 ← S0 electronic transition defines the adiabatic excitation energy to be 36, 987 ± 4 cm −1 based on the resonance-enhanced one-color two-photon ionization spectrum of m-BrFPh. And adiabatic ionization potential (IP) of 73, 903 ± 8 cm −1 is determined from band origin in the SEVI spectra. Meanwhile, the computed frequencies are in excellent agreement with the experimental observations and Franck-Condon simulations are performed to aid us to confidently assign major vibrational modes in S1 and D0 states. And the changes in the wavenumber of the vibrational modes upon S1 ← S0 and D0 ← S1 transitions are examined. Furthermore, the mixing of vibrational modes both between S0 & S1 and between S1 & D0 has been discussed. Graphical abstract: Image, graphical abstract